Low co-existence rates of Lactobacillus spp. and Helicobacter pylori detected in gastric biopsies from patients with gastrointestinal symptoms Bajas tasas de coexistencia de Lactobacillus spp. y Helicobacter pylorien biopsias gástricas de pacientes con síntomas gastrointestinales - Apolinaria García; Katia Sáez; Carolina Delgado; Carlos L. González (Revista Espanola de Enfermedades Digestivas, 2012)
Background: bacterial diversity of the stomach includes various species. Among them, Helicobacter pylori, a microorganism which has been associated to gastric diseases, is frequently isolated in this habitat. In addition, Lactobacillus spp., a genus including probiotic strains, has also been documented in this habitat. The co-existence of these two species in the stomach of symptomatic patient needs to be elucidated. Aims: our goal was to establish if Lactobacillus spp. and H. pylori co-exist in the stomach mucosa of symptomatic patients. Methods: gastric biopsies (antrum and/or the body) from 427 Chilean patients with gastrointestinal discomfort were analyzed. The H. pylori infection and/or Lactobacillus spp. colonization status was determined for each patient by standard culture techniques, and statistical correlations between the presence of those species and the age, gender, or the severity of the gastric disease were also established. Results: only 6.1% of the samples presented co-existence of Lactobacillus spp. and H. pylori. This former species was isolated in 42.6% of the patients as unique species, while Lactobacillus spp. was isolated as single species in 19.4% of the individuals. Chronic non-atrophic gastritis was prevalent in Lactobacillus spp. non colonized individuals, while chronic non-atrophic and chronic atrophic gastritis diagnosis was similar in Lactobacillus spp. harbouring individuals (p < 0.001). The presence of Lactobacillus spp. significantly increased with age (p = 0.005), independently of gender. Conclusion: the negative Pearson correlation between Lactobacillus spp. and H. pylori(r = -0.112, p = 0.020) indicates that the co-existence of both species is low in human gastric mucosa of symptomatic patients.